2021
DOI: 10.1093/nar/gkab913
|View full text |Cite
|
Sign up to set email alerts
|

NPCDR: natural product-based drug combination and its disease-specific molecular regulation

Abstract: Natural product (NP) has a long history in promoting modern drug discovery, which has derived or inspired a large number of currently prescribed drugs. Recently, the NPs have emerged as the ideal candidates to combine with other therapeutic strategies to deal with the persistent challenge of conventional therapy, and the molecular regulation mechanism underlying these combinations is crucial for the related communities. Thus, it is urgently demanded to comprehensively provide the disease-specific molecular reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…Meanwhile, for the treatment of several medical conditions, supplements of herbal drugs are used around the world. These are used in combination with drugs or used alone [ 149 ]. In some cases, the combined use of herbs and drugs may alter the pharmacokinetic profile of drugs [ 150 ].…”
Section: Herb–drug Interactionmentioning
confidence: 99%
“…Meanwhile, for the treatment of several medical conditions, supplements of herbal drugs are used around the world. These are used in combination with drugs or used alone [ 149 ]. In some cases, the combined use of herbs and drugs may alter the pharmacokinetic profile of drugs [ 150 ].…”
Section: Herb–drug Interactionmentioning
confidence: 99%
“…and presenting interactions in a variety of attractive visualisations. NPCDR ( 90 ) works in a similar area but focuses on cases where at least one of the drugs involved is based on a natural product. Cellular responses to drugs are captured by the new CeDR database ( 91 ), which uses single cell transcriptomics data to capture the characteristic drug responses of different cells and tissues, in human and mouse and in health and disease.…”
Section: New and Updated Databasesmentioning
confidence: 99%
“…These limitations incline studies toward the development of new therapies based on natural products combined with conventional clinically-used chemotherapeutic drugs. The clinical goal of the combination treatment is to reduce the dose of the active drug while preserving its efficacy or reducing toxicity [ 71 ]. Numerous studies both on in vitro and in vivo models of cancer have reported potentiation of the activity of clinical drugs such as CDDP, 5-fluorouracil, doxorubicin, paclitaxel, gemcitabine, and imatinib by natural compounds e.g., alkaloids, terpenoids, steroids, polyphenols, and flavonoids, including our previous reports [ 48 , 72 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%